Atomic Regulation of PGM Electrocatalysts for the Oxygen Reduction Reaction - Wu, Menghao; Chen, Changli; Zhao, Yizhou; Zhu, Enbo; Li, Yujing (Frontiers in Chemistry, 2021)
With the increasing enthusiasm for the hydrogen economy and zero-emission fuel cell technologies, intensive efforts have been dedicated to the development of high-performance electrocatalytic materials for the cathodic oxygen reduction reaction (ORR). Some major fundamental breakthroughs have been made in the past few years. Therefore, reviewing the most recent development of platinum-group-metal (PGM) ORR electrocatalysts is of great significance to pushing it forward. It is known that the ORR on the fuel cell electrode is a heterogeneous reaction occurring at the solid/liquid interface, wherein the electron reduces the oxygen along with species in the electrolyte. Therefore, the ORR kinetic is in close correlation with the electronic density of states and wave function, which are dominated by the localized atomic structure including the atomic distance and coordination number (CN). In this review, the recent development in the regulation over the localized state on the catalyst surface is narrowed down to the following structural factors whereby the corresponding strategies include: the crystallographic facet engineering, phase engineering, strain engineering, and defect engineering. Although these strategies show distinctive features, they are not entirely independent, because they all correlate with the atomic local structure. This review will be mainly divided into four parts with critical analyses and comparisons of breakthroughs. Meanwhile, each part is described with some more specific techniques as a methodological guideline. It is hoped that the review will enhance an insightful understanding on PGM catalysts of ORR with a visionary outlook.